Eksplorasi Pengalaman Guru dalam Menggunakan Media Digital untuk Meningkatkan Motivasi Siswa dalam Pembelajaran IPA - Juneda, Juneda; Dinda Saskia; Devi Margaretta (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2025)
The purpose of this study was to clarify the experience of teachers in using digital learning media to improve student motivation when studying natural science (IPA) at SDN 106162 Medan Estate. Three main aspects were found in this study based on the results of the analysis. First, the implementation of science learning is carried out in accordance with the Learning Implementation Plan (RPP). Second, teachers use a combination of traditional and digital media to support the learning process. Third, the use of digital media has a positive effect on student motivation. This is due to increased participation, enthusiasm, and understanding of science concepts. Digital media such as interactive learning videos, educational applications, and virtual simulations can help students understand the material in a more interesting and engaging way. However, the implementation of digital media in learning is not only the need for teacher training when using technology, but also challenges such as limited devices and internet access. This study emphasizes the importance of infrastructure and training support to improve the use of digital media in elementary school science learning.